EFFECT ORGANIC NUTRIENT HUMIC AND COMPOUND CHEMICAL FERTILIZER IN LEAVES CONTENT FROM ELEMENTS AND TOTAL YIELD CUCUMBER - & AL-IBADI, AL-AZZAWI (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment was carried out at the Scientific Research Station of the College of Agriculture - University of Baghdad (Al-Jadiriyah), Spring and Autumn seasons 2015, using to Cucumber hybrid Gazeer, to study effect of adding organic material the vegetative growth of Cucumber. The experiment was conducted as factorial experiment (4x3) with in randomized complete Block design, with three replicates, First factor includes four levels of chemical fertilizer (0, 100%, 50% and 25%) of the recommended doses of fertilizers, The second factor was three levels of organic nutrient humic (0, 5kg ha-1 and 10kg ha-1). The results showed superiority of the treatment of interaction C1H2 (NPK 100%+10 kg.ha-1 nutrient organic) in leaves content (2.63 and 2.70)%, Phosphorus (0.49 and 0.53)%, Potassium (3.69 and 3.50)%, Magnesium (0.81 and 0.77)%, Iron (192.84 and 187.71) mg kg-1 and Zinc (51.97 and 52.67) mg kg-1, also the same treatment was superiority in total production (42.51 and 30.50) tons for two seasons, spring and autumn respectively.